Administrating the cultural organization (using the example of M. Oyun Culture and Recreation Center in Turan) - Lekishvili, Anna V. (The New Research of Tuva, 2014)
Article presents the authors opinion about the prospects of developing the houses of culture in villages and towns. It describes the experience of M.Oyun Culture and Recreation Center in the town of Turan (Republic of Tyva).